Characterization of a chitinase from Trichinella spiralis and its immunomodulatory effects on allergic airway inflammation in mice - Jia Xu; Ye Yao; Qisheng Zhuang; Zixuan Li; Min Zhang; Shouan Wang; Hongxin Hu; Jianbin Ye (Parasites & Vectors)
Abstract Background A fundamental tenet of the hygiene theory is the inverse association between helminth infections and the emergence of immune-mediated diseases. Research has been done to clarify the processes by which helminth-derived molecules can inhibit immunological disorders. This study aimed to evaluate the ability of Trichinella spiralis chitinase (Ts-chit) to ameliorate the symptoms of allergic airway inflammation. Methods Recombinant Trichinella spiralis chitinase (rTs-chit) was expressed in Escherichia coli BL21, and its structural homology to murine acidic mammalian chitinase (AMCase) was comprehensively analyzed. The expression of Ts-chit was examined across all T. spiralis life stages. To explore its immunomodulatory potential, a murine model of allergen-induced airway inflammation was established. The effects of rTs-chit were evaluated by assessing airway hyperresponsiveness and cytokine profiles in bronchoalveolar lavage fluid and performing detailed histopathological and immunohistochemical analyses. Results Recombinant Ts-chit (rTs-chit) was successfully expressed in E. coli BL21, showing strong structural similarity to murine acidic mammalian chitinase (AMCase). Expression profiling revealed that Ts-chit is present throughout all stages of the T. spiralis life cycle. In an allergic airway inflammation model, rTs-chit reduced weight loss and lung inflammation, lowering inflammatory cell infiltration and Th2 cytokines (IL-4, IL-5, IL-13) while increasing the immunosuppressive cytokine IL-10. Additionally, rTs-chit treatment decreased the expression of GATA3, arginase-1, MCP-1, CCL-11, and AMCase, along with reducing OVA-specific IgE, IgG, and IgG1 levels, suggesting its potential as an immunomodulatory agent. Conclusions This study highlights rTs-chit’s potential as a therapeutic agent for allergic airway diseases, leveraging its structural similarity to host chitinases to regulate Th2 responses and inflammatory pathways. The findings provide new insights into helminth-derived proteins as promising candidates for immune-based therapies. Graphical Abstract